(untitled) (Colloquium Vitae. ISSN: 1984-6436, 2023)
SARS-CoV-2 is the etiologic agent of the pandemic started in December 2019 and has been reaching alarming numbers worldwide. Neurological manifestations have been reported and must be highlighted. This study reports cases of severe neurological manifestations associated with COVID-19 in patients admitted to a tertiary hospital. The first patient was referred with history of generalized seizures after the diagnosis of COVID-19; imaging exam indicated cerebral venous thrombosis. The second patient, already treated for COVID-19, developed pain in the dorsal region, progressing to ascending paresthesia, and had diagnosis of Guillain-Barré Syndrome, with fatal outcome. The third patient, also with fatal outcome, presented with headache and left hemiparesis. After imaging exams, was discharged, but days after, returned with mental confusion and the hypothesis of encephalitis was confirmed. SARS-CoV-2 infection was confirmed after death. The main objective of this study is to report severe neurological manifestations related to COVID-19.